Non-Hydrothermal Synthesis of Cylindrical Mesoporous Materials: Influence of the Surfactant/Silica Molar Ratio - Deicy Barrera; Jhonny Villarroel-Rocha; Luis Marenco; Marcos I. Oliva; Karim Sapag (Adsorption Science & Technology)
Ordered mesoporous materials of MCM-41 and SBA-15 type were synthesized under non-hydrothermal conditions using different molar ratios of surfactant/silica, ranging from 0.07 to 0.27 for MCM-41 and from 0.009 to 0.021 for SBA-15. Nitrogen adsorption/desorption isotherms at 77 K were used to evaluate the specific surface areas, with values up to 1450 m 2 /g and 1100 m 2 /g being obtained for MCM-41 and SBA-15, respectively. Scanning electron microscopy was carried out to study the morphology of the materials. The sizes of the primary mesopores and the pore thicknesses were assessed by a geometrical method using X-ray diffraction and nitrogen adsorption data. The results for the pore sizes were compared with those obtained by a recently reported method (VBS-method) and the Non-Local Density Functional Theory (NLDFT) model, both proposed to evaluate the pore-size distribution of these materials. It was found that, under the synthesis conditions, the surfactant/silica molar ratio had an important effect on the final characteristics of these materials.